Crown condition assessment at the CONECOFOR Permanent Monitoring Plots - Renzo NIBBI; Davide BETTINI; Enrico CENNI; Marco FERRETTI; Filippo BUSSOTTI; Alberto COZZI (Journal of Limnology, 2002)
A detailed crown condition assessment is currently being carried out at the CONECOFOR (CONtrollo ECOsistemi FORestali, Control of Forest Ecosystems) plots. The assessment began in 1996, and during the first two years (1996 and 1997) an assessment form based on previous regional experience was used; in 1998 the new official EU form was adopted. The resulting loss of comparability means that only a few indices can be used in the temporal series 1996-1999. Much effort was devoted to Quality Assurance (QA) procedures. The QA program is structured as follows: (i) specific field manuals have been adopted and are continuously updated; (ii) a national training and intercalibration course (NT&IC) is undertaken yearly before beginning the assessment campaign;( iii) field checks are carried out yearly on a large number of plots. The results of the QA program have shown that for several indices the quality objectives were not reached, but the quality of the data is improving with time. To express the change in crown conditions in each area, a complex index (CCI = Crown Condition Index) was adopted. This index is the result of the sum of the relativized values of all the common indices used during the four years. The following parameters were used: transparency, ramification type, leaf colour alteration extension, leaf damage extension, alteration of leaf distension extension. The range within which the CCI fluctuates was evaluated taking into account all the observations carried out at a given plot throughout the years. The number of cases over a given threshold (outliers) was calculated for each year. The threshold for outliers was calculated as the median value plus 2 times the range of the interquartile value. All individual cases exceeding this value are considered outliers. The results are presented for all the areas in which the data set is complete for the four years. The yearly fluctuations are discussed and related to possible causes.